Math, asked by krishnanarayan07103, 11 months ago

18 Simplify
(3+√3)(3-√3)÷(2+ √2)(2-√2)

Answers

Answered by ajithameekhal
1

Answer:

answer is 3

Step-by-step explanation:

we know that,

(a + b)(a - b) = a²- b²

∴ (3 +√3)(3 -√3) = 3² - √3²

                        = 9 - 3    [√3² = √3 x √3 = 3]

                        = 6

  (2+ √2)(2-√2) = 2² - √2²

                        = 4 - 2    [√2² = 2]

                        = 2

ie, (3+√3)(3-√3)÷(2+ √2)(2-√2) = 6 ÷ 2

                                               = 3

Similar questions